Vaccines distribution system at primary healthcares in the special region of Yogyakarta - Dian Medisa; Diesty Anita Nugraheni (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
Background: Vaccine cold-chain distribution system must be monitored to guarantee the vaccine quality. Improper vaccine distribution system can cause damage and loss of efficacy. Therefore, the Indonesian government released some regulations to manage the vaccine cold-chain system, including the Good Distribution Practices for Pharmaceutical Products (Cara Distribusi Obat yang Baik/CDOB) in 2012 and Regulation of the Minister of Health Number 42 in 2013 (PMK 42/2013). Objective: The purpose of this study was to evaluate the implementation of the vaccine distribution system in primary healthcare (PHCs). Methods: A survey was conducted in 30 PHCs in the Special Region of Yogyakarta. Data were collected by observing the vaccine distribution system in PHCs using checklists developed based on CDOB 2012 and PMK 42/2013.Results: The study showed that the personnel in 24 PHCs (80%) checked the condition of the temperature monitoring device and Vaccine Vial Monitor (VVM) while receiving the vaccines. Furthermore, all PHCs (100%) had both cool packs and vaccine carriers, whereas those having cold packs were only 2 (7%). First expired - first out (FEFO) and first in - first out (FIFO) systems were implemented in 30 (100%) and 28 (93%) PHCs, respectively. Conclusion: The results indicated that most of the PHCs in Yogyakarta Special Region had implemented a good vaccine distribution system, yet they still need improvement especially in vaccine recording procedures.